MARJI‘ ḌAMĪR AYAT YAHDĪ MAN YASHĀ` DAN YUḌILLU MAN YASHĀ: Studi Komparatif Antara Terjemah al-Quran dan Tafsir Ringkas Lajnah Pentashihan Mushaf al-Quran (LPMQ) Kemenag - Muchammad Zahrul Anam; Abdul Ghofur Maimoen (AL ITQAN: Jurnal Studi Al-Qur'an, 2020)
The distribution of the Quran Muṣḥaf in Indonesia is monitored by an institution called Lajnah Pentashihan Muṣḥaf al-Qur'an (LPMQ - Mushaf Quran Confirmation Committee). They are tasked with researching and preventive safeguarding of the Mushaf Quran. Apart from these duties, LPMQ also carries out activities related to the Quran in the form of translation and interpretation and matters related to other Quranic verses. Many people eagerly welcomed it, even the majority used LPMQ works to ease the understanding of the Quran because the redaction this Quran tends to be brief, dense yet has broad meaning. and often it use ḍamīr in order to be more concise, so it needs a deep knowledge till there is no misinterpretation. In addition to adding insight, this article also emphasizes that interpretation and translation activities must not be based on the subjectivity of the interpreter and translator, but through a process based on mu'tabar principles or agreed legal rules. This research uses the theory of marji ḍamīr of Khālid Uthman Thabt to see the consistency of the Kemenag (Ministry of Religion translator team) in terms of marji ḍamīr. Based on data analysis, it is concluded that both in translation and interpretation, LPMQ remains consistent with existing procedures regarding the legality of activities related to Quranic verses both in terms of linguistic and naḥwu (grammatical) principles, besides that this work is the piece of result of moderate thinking, the collective work of various brilliant thinkers. Keywords: Marji‘ ḍamīr, Translation of Quran, LPMQ, Consistency.